A review of the enhancement of solar thermal collectors using nanofluids and turbulators. (5th February 2023) - Aissa, Abderrahmane; Qasem, Naef A.A.; Mourad, Abed; Laidoudi, Houssem; Younis, Obai; Guedri, Kamel; Alazzam, Anas
Highlights: Review the recent advancements in integrating nanofluids and turbulators into Solar thermal collectors. Summarize the experimental and numerical studies on hybrid nanofluids-turbulator solar systems. Detail numerous strategies and approaches to improve the performance of solar thermal systems by introducing turbulators and by using different nanofluids. Future suggestions are made for nanofluids/turbulator solar thermal system development. Abstract: Nanofluids are viewed as an effective way to increase the efficiency of solar energy systems. Their importance is illustrated by enhancing the thermal conductivity of heat transfer fluids. Incorporating fins and turbulators in the solar system is another method for enhancing heat transmission to the carrying fluid. The simultaneous use of nanofluids and turbulators is a promising approach to improve solar system performance. Thus, this paper investigates, discusses, and emphasizes the significance of combining the effect of employing nanofluids and turbulence generators in solar collectors to increase thermal performance and extract more useable solar energy. This paper provides an overview of recent advancements in this area, the systems that have been built, and their future uses within the solar energy industry. The proposed geometries for turbulators, their improvement in overall performance, and the employed nanofluids are presented and reviewed. Finally, outstanding recent developments and future prospects in the hybrid nanofluids-turbulators system are discussed. This article provides a comprehensive assessment of the essential issues on which the hybrid nanofluids-turbulators systems might throw light on building relevant systems.